African Studies in the Academy : The Cornucopia of Theory, Praxis and Transformation in Africa? - Mubaya, Tapuwa R.; Mawere, Munyaradzi (Book collections on Project MUSE., 2017)
For a long time, African Studies as a discipline has been spearheaded by academics and institutions in the Global North. This puts African Studies on the continent at a crossroads of making choices on whether such a discipline can be legitimately accepted as an epistemological discipline seeking objectivity and truth about Africa and the African peoples or a discipline meant to perpetuate the North's hegemonic socio-economic, political and epistemic control over Africa. The compound question that immediately arises is: Who should produce what and which space should African Studies occupy in the academy both of the North and of the South? Confronted by such a question, one wonders whether the existence of African Studies Centres in the Global North academies open opportunities for critical thinking on Africa or it opens possibilities for the emergence of the same discipline in Africa as a fertile space for trans-disciplinary debate. While approaches critical for the development of African Studies are pervasive in African universities through fields such as cultural studies, social anthropology, history, sociology, indigenous knowledge studies and African philosophy, the discipline of African Studies though critical to Africa is rarely practised as such in the African academy and its future on the continent remains bleak. African Studies in the Academy is a testimony that if honestly and objectively practised, the crossroads position of African Studies as a discipline makes it a fertile ground for generating and testing new approaches critical for researching and understanding Africa. It also challenges Africa to seriously consider assuming its legitimate position to champion African Studies from within. These issues are at the heart of the present volume.